2017
DOI: 10.1111/manc.12200
|View full text |Cite
|
Sign up to set email alerts
|

Partial Privatization of State Holding Corporations

Abstract: We consider a state holding corporation with two plants that may produce complementary or substitute goods and that competes with one or two private firms. We find that the government partially privatizes the two plants of the state holding corporation and is indifferent between selling them partially to a single investor and to different investors. However, in the former case the government retains a greater (smaller) stake in the state corporation if goods are substitutes (complements).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 38 publications
1
17
0
1
Order By: Relevance
“…Matsumura (1998) pointed out that neither full privatization nor full nationalization is the optimum. Nakamura (2018) and Dong, Barcena-Ruiz, and Garzon (2018) found that the optimal degree of privatization in mixed economy varies in accordance to product differentiation. Matsumura and Kanda (2005) argued that full nationalization could be the optimal strategy under given conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Matsumura (1998) pointed out that neither full privatization nor full nationalization is the optimum. Nakamura (2018) and Dong, Barcena-Ruiz, and Garzon (2018) found that the optimal degree of privatization in mixed economy varies in accordance to product differentiation. Matsumura and Kanda (2005) argued that full nationalization could be the optimal strategy under given conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Lee and Wang (2018) find that the timing of privatization influences the optimal degree of privatization. Dong, Barcenaruiz, and Garzon (2018) show that whether the product is a substitute or a complementary product affects the degree of privatization. Chang, Wu, and Lin (2018) find that the level of the regulated price affects the optimal privatization of a public enterprise under exogenous price control.…”
Section: Introductionmentioning
confidence: 99%
“…To explain this evidence, the literature on mixed oligopoly has analyzed the decision by governments of whether to privatize a single public firm (see, for example, De Fraja andDelbono, 1989, 1990;Corneo and Jeanne, 1994). These papers have been extended to consider, among other factors, partial privatization of public firms (Matsumura, 1998;Lin and Matsumura, 2012), privatization and mergers (Méndez-Naya, 2007, 2012, privatization of state-holding corporations (Bárcena-Ruiz and Garzón, 2017;Dong et al, 2018), and privatization with switching costs (Dong and Bárcena-Ruiz, 2017).…”
Section: Introductionmentioning
confidence: 99%